Climate Change and Energy Security : The Dilemma or Opportunity of the Century? - Cevik, Serhan (Washington, D.C. : International Monetary Fund, 2022)
This paper investigates the connection between climate change and energy security in Europe and provides empirical evidence that these issues are the two faces of the same coin. Using a panel of 39 countries in Europe over the period 1980-2019, the empirical analysis presented in this paper indicates that increasing the share of nuclear, renewables, and other non-hydrocarbon energy and improving energy efficiency could lead to a significant reduction in carbon emissions and improve energy security throughout Europe. Accordingly, policies and reforms aimed at shifting away from hydrocarbons and increasing energy efficiency in distribution and consumption are key to mitigating climate change, reducing energy dependence, and minimizing exposure to energy price volatility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Energy and the Macroeconomy; Energy; Global Warming; Natural Disasters and Their Management